Safety and efficacy of Beltherm MP/ML (endo‐1, 4‐beta‐xylanase) as a feed additive for piglets, pigs for fattening and other porcine species. (5th March 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Beltherm MP/ML contains endo‐1, 4‐beta‐xylanase and it is to be used as a zootechnical additive for weaned piglets, pigs for fattening and minor porcine species for fattening. The safety and efficacy of the additive when used for poultry species have been evaluated previously by the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP Panel). In that assessment, the safety for the consumers, environment and the users was assessed. The applicant has requested for the authorisation in new species/categories. The Panel considered that the new use would not introduce hazards that have not already been considered. Therefore, it was concluded that the additive is safe for the consumers and the environment. Considering the safety for the user, the Panel concluded that the additive, in either form, is not toxic by inhalation or irritant for skin or eye but it is considered a potential respiratory sensitiser. The Panel could not conclude on the dermal sensitisation potential of the additive. In a trial with weaned piglets, the animals tolerated well a 200‐fold the level recommended in feed by the applicant; therefore, the Panel concluded that the additive is safe for weaned piglets, pigs for fattening and minor porcine species at the recommended level. Based on the data provided to support the efficacy of the additive in weaned piglets and pigs for fattening, the Panel concluded that the additive has the potential to be efficacious at the recommended level in those species/categories. The conclusions on the safety and efficacy for weaned piglets and pigs for fattening were extrapolated to minor porcine species.